Process of Problem Solving in Physics in the Context of Projectile Motion - PRABHA, SHASHI (SCHOOL SCIENCE, 2006)
When solving the problems in Physics, multiple ideas come to the mind of the learners (Gandhi, Varma, 2004) .They try to fit the problem in their existing cognitive schemes.  They try to correlate the problem with their earlier experiences.They describe the problem by identifying the given quantities and the quantity/quantities to be found out. ● They prepare suitable hypothesis for solving the problem.  They plan for action by identifying scientific principles and formula to be applied in the given situation. They analyse and/ or synthesise the relationship between the components of the  problem and form a mental model of the relationship and concept.